Dilemma of diagnosing OCD: a case report - Ridzwan, Hijaz; Tuan Mohamad, Tengku Mohd Saifuddin (Malaysian Psychiatric Association, 2017)
Obsessive Compulsive Disorder (OCD) may present in the prodromal phase of schizophrenia. However at times it is difficult to distinguish between the pure obsession and psychotic obsessions that exist in patients. We present a case of a patient initially diagnosed as Schizophrenia due to the disorganized aspect of her behaviour, only to discover an extreme form of obsessions that explained her demeanor throughout